Treatment of canine non-indolent T cell lymphoma using the VELCAP-TSC protocol: A retrospective evaluation of 70 dogs (2003–2013). (May 2016) - Goodman, Ingrid H.; Moore, Antony S.; Frimberger, Angela E.
Highlights: Seventy dogs with T cell lymphoma were treated with an alkylator-rich chemotherapy protocol. Complete remission was more likely in neutropenic dogs than dogs with neutrophilia. Dogs in a complete remission had significantly longer progression free survival than dogs not in complete remission. Overall survival was shorter in Boxers than other breeds and in dogs that were in substage b (unwell). The 1 and 2 year survival rates were 31% and 20.2% after commencing chemotherapy. Abstract: The immunophenotype of canine non-indolent lymphoma has prognostic value; dogs with T cell lymphoma have a poorer response rate and shorter survival times than dogs with B cell lymphoma. This study sought to retrospectively evaluate prognostic factors for complete remission (CR), progression free survival (PFS) and overall survival time (OST) in 70 dogs with T cell lymphoma treated with an alkylator-rich, combination protocol. The overall remission was 72.9%; 45 dogs (64.3%) achieved CR and six (8.6%) achieved partial remission. Dogs that were neutropenic at diagnosis were significantly more likely to achieve CR. The median overall PFS was 175 days; 1, 2 and 3 year PFS were 26.8%, 15.8%, and 12.6%, retrospectively, after commencing chemotherapy. Median PFS was significantly longer for dogs that achieved CR. Median OST was 237 days. The 1, 2 and 3 year survival rates were 31%, 20.2% and 11.5%, retrospectively, after commencing chemotherapy. The median OST was significantly longer for dogs that achieved CR and significantly shorter for Boxers and those in substage b at diagnosis. More than 30% of dogs treated with this protocol survived >1 year, suggesting that favourable outcomes and longer survival are possible for a proportion of dogs with T cell lymphoma.